The sodium diffusion during the debittering of green table olives. Elliptical coordinates model - Maldonado, Mariela; Perez, Raul Cesar; Perez Iglesias, José I. (Timeland Publication, 2019)
Many models had been develops in order to study the diffusion process in fruits. All they were consistent, but they none fits exactly to the shape of the geometry of the fruit. We had developed a new model into elliptical coordinates in order to can study the diffusion process in ovoid fruits. Its results has a very good agree with the experimental measure that we had made to table olive. It has an annex benefit: when the model is used, the diffusion coefficient value at different time can to calculate to pulp of the ovoid fruits.